2021
DOI: 10.1186/s43094-021-00235-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical stability and degradation kinetics of bedaquiline in hydrolytic solutions of different pH

Abstract: Background Tuberculosis is an infection that has high mortality rate in human as well as in animals if it remains unattained for long time. Scientists are always desirous to discover new molecules against Mycobacterium tuberculosis; one of them is bedaquiline which was recently approved to treat multidrug resistance TB. During the clinical study of new molecule stability and impurity are the key aspects to develop formulation. Stability issues in bulk drug are dangerous to drug safety and needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This advancement in degradation study requires the study of degradation kinetic data to evaluate deviation from normal degradation kinetic of drug substance and drug product. (1984), Lerner et al (1988), Oliveira et al (2013Oliveira et al ( , 2016, Paczkowska et al (2015), Rajput and Vanavi (2021) degradation of pharmaceuticals. The basis of change in chemical kinetics includes the formation of a product that can further increase or decrease the rate of drug degradation reaction.…”
Section: Degradation Kinetic Study Of Pharmaceuticals Employing Advan...mentioning
confidence: 99%
“…This advancement in degradation study requires the study of degradation kinetic data to evaluate deviation from normal degradation kinetic of drug substance and drug product. (1984), Lerner et al (1988), Oliveira et al (2013Oliveira et al ( , 2016, Paczkowska et al (2015), Rajput and Vanavi (2021) degradation of pharmaceuticals. The basis of change in chemical kinetics includes the formation of a product that can further increase or decrease the rate of drug degradation reaction.…”
Section: Degradation Kinetic Study Of Pharmaceuticals Employing Advan...mentioning
confidence: 99%
“…Literature survey for analytical data of BDQ showed that spectrophotometric method ( 5 ), forced degradation study ( 6 ), simultaneous estimation ( 7 , 8 ), bio-analytical HPLC/MS methods ( 9 , 10 ), chiral analysis ( 11 , 12 ), pharmacokinetic study ( 13 , 14 ) and simultaneous bio-analytical analysis ( 15 ) have been reported till date. The only one reported stability study ( 6 ) does not report the identification of DPs or process related impurities of BDQ.…”
Section: Introductionmentioning
confidence: 99%